A compact heat recirculating spiral geometry for thermal integration for Sabatier reaction in microreactor. Issue 8 (30th April 2022) - Raghu, Aswathy K.; Kaisare, Niket S.
Abstract: Sabatier reaction, the catalytic reduction of CO2 to methane, is a reversible and exothermic reaction that produces CO as a by‐product. We use two‐dimensional computational fluid dynamics (CFD) simulations to analyze the performance of a three‐turn spiral microreactor, useful for portable or modular applications. Spiral reactor has inlet at the center followed by three turns that spirals outwards. It allows thermal integration via co‐current self‐coupling of Sabatier reaction, which enables utilizing the exothermic heat of methanation for preheating of the cold reactants by hot products. Due to compact nature of the geometry, heat released spreads out in the reactor causing an overall moderation of temperature. A favorable cooling effect is achieved in spiral geometry without using external cooling or feed dilution, merely by the property of reactor configuration. For the base case, 71% conversion with 92.6% selectivity to CH4 is attained. Comparison with counter‐current operating strategy in U‐bend reactor is presented.